A laboratory treadmill for simulation of road surface induced vibrations in cycling - Buder, J.; Sanseverino, G.; Odenwald, S.; Schwanitz, S. (Journal of Science and Cycling, 2023)
Within the framework of a systematic approach, a novel test setup for the simulation of road surface induced vibrations was developed. This can be used for various questions concerning the oscillatory system cyclist-bicycle. The innovation compared to the state of the art is the separate introduction of vibrations at the front and rear wheel while at the same time enabling a natural riding behavior during pedaling and coasting, even at higher speeds.